Rockly Bay, Tobago - (:unkn) unknown (My University, 2011)
The postcard shows coconut palms swaying in the breeze on Rockly Bay in Tobago.
Colour: Black and white; Style: Portrait; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Bays--Trinidad and Tobago; [1950]; Coconut palm--Trinidad and Tobago; Seashore--Trinidad and Tobago; Coasts--Trinidad and Tobago